Communication networks and team performance: selecting members to network positions - Guo, Jerry; Argote, Linda; Kush, Jonathan; Park, Jisoo (Frontiers in Psychology, 2023)
This study examines how individuals come to occupy communication network positions and the effect of selection processes on group performance. Drawing on the Carnegie perspective and research on communication networks, we compare the performance of groups whose members receive their choice of who occupies which network position to the performance of groups whose members do not receive their choice. We integrate ideas from the Carnegie perspective with the social psychological literature on the recognition of expertise to theorize that when group members choose who occupies which network positions, individuals select themselves and others into network positions that best suit their skillsets. The selection process allows groups to match individual member expertise to network position, thereby improving performance. We test this hypothesis in a laboratory study manipulating how members are assigned to positions in a centralized communication network. We find individuals who communicate more during training are more likely to be chosen as the central member, and that their communication activity explains the effect of choosing the central member on performance. Supplemental analyses suggest that groups allowed to select their central member performed as well as, and often better than, groups whose central member was randomly assigned. Our results contribute to the Carnegie perspective by demonstrating that the intra-team processes that develop a team’s network help explain their performance.